A grounded coplanar waveguide resonator based in-line material characterization sensor - Talai, Armin; Mann, Sebastian; Weigel, Robert; Koelpin, Alexander (2016 German Microwave Conference (GeMiC), 2016)
Microwave Materials such as Rogers RO3003 are subject to process-related fluctuations in terms of the relative permittivity. The behavior of high frequency circuits like patch-antenna arrays and their distribution networks is dependent on the effective wavelength. Therefore, fluctuations of the relative permittivity will influence the resonance frequency and antenna beam direction. This paper presents a grounded coplanar wave-guide based sensor, which can measure the relative permittivity at 77 GHz, as well as at other resonance frequencies, by applying it on top of the manufactured depaneling. In addition, the sensor is robust against floating ground metallizations on inner printed circuit board layers, which are typically distributed over the entire surface below antennas.